Analyzing the factors influencing satisfaction and continuous use intention of Chinese government WeChat official accounts: Applying SEM approach - Lai, Xianghui; Wang, Yan; Ye, Mengting; Zhuang, Guoxin; Li, Ze; Lin, Guosong; Lin, Xiaoping (Journal of Electrical Systems, 2024)
Government WeChat official accounts (GWOAs) have been increasingly and widely adopted by Chinese government agencies to provide public services for the people. However, there is a lack of research concentrating on this subject; Methods: Based on 714 user survey results, the satisfaction and sustained intention models of GWOA were evaluated using Structural Equation Modeling (SEM); Results: factors including perceived usefulness, perceived ease of use, expectation confirmation, and network externality can positively affect GWOAs satisfaction and continuance, while the factor, perceived risk, can have negative effect on them. In the mediating effect analysis, users' satisfaction of GWOAs mediates the effects of perceived ease of use and perceived usefulness on GWOAs continuous use intention; network externality mediates the effects of perceived risk on GWOAs continuous use intention; users' both perceived usefulness and satisfaction of GWOAs mediate the effects of expectation confirmation on GWOAs continuous use intention.; Conclusions: perceived usefulness, perceived ease of use, expectation confirmation, network externality and perceived risk have been significant to determine users' satisfaction and continuous use intention of GWOAs. This research has potential application value in helping the government agencies, as operators of GWOAs, to enhance users' satisfaction and continuous use intention of GWOAs.